2012
DOI: 10.1103/physrevb.85.094411
|View full text |Cite
|
Sign up to set email alerts
|

Neutron scattering study of the magnetic microstructure of nanocrystalline gadolinium

Abstract: We report grain-size-dependent results on nanocrystalline bulk Gd obtained by magnetic small-angle neutron scattering (SANS) and magnetometry. This approach allows one to study systematically how the magnetic microstructure of this rare-earth metal is affected by defects in the atomic microstructure, which are largely present in nanocrystalline materials, predominantly in the form of grain boundaries. The neutron scattering data reveal two types of angular anisotropies in the magnetic-field-dependent scatterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 55 publications
2
55
1
Order By: Relevance
“…The parameter l C has been determined in the usual way as the value of r for which C(r) has decayed to exp(À1) of its value C(r = 0) at the origin, where the latter is obtained by extrapolation of the C(r) data; this extrapolation, from C(r min ) to C(r = 0), has been done using different functional dependencies (linear and quadratic), and the results for l C agree within 2-3 nm (for further details, see Refs. [23,24]). Fig.…”
Section: Figmentioning
confidence: 97%
“…The parameter l C has been determined in the usual way as the value of r for which C(r) has decayed to exp(À1) of its value C(r = 0) at the origin, where the latter is obtained by extrapolation of the C(r) data; this extrapolation, from C(r min ) to C(r = 0), has been done using different functional dependencies (linear and quadratic), and the results for l C agree within 2-3 nm (for further details, see Refs. [23,24]). Fig.…”
Section: Figmentioning
confidence: 97%
“…The increase of magnetic properties of nanocrystalline magnets is mainly attributed to the ultrafine nanograin microstructure [31][32][33]. On one hand, it has been found that the coercivity of nanocrystalline alloy increases first and then decreases with the decrease of grain size on the nanoscale [34].…”
Section: Characterization Of Magnetic Performancementioning
confidence: 99%
“…There is a linear behavior which can be connected to a reduction of the Tb 3+ magnetic moment can be explained by the existence of a spin disorder layer at the surface of the particles. In this sense, and as was also applied in other nanoparticle systems [30,31,32], the width of this surface layer can be estimated from the plot of M S vs the inverse of the mean diameter of the particles (1/D), assuming a core-shell structure in which the non-magnetic shell has a constant thickness (t). The behaviour of this relationship is well accounted by the expression M S = M bulk (1 − 6t/D) [30], being t = 0.8 nm in the case of the TbAl 2 alloys.…”
Section: Specific Heat and Magnetisationmentioning
confidence: 99%